Bifurcation Behavior in Oscillations during H2O2 Reduction at Pt Electrodes. (10th January 2017) - Mukouyama, Yoshiharu; Hara, Daisuke; Kawasaki, Hirokazu; Kikuchi, Mitsunobu; Yamada, Yuri; Nakanishi, Shuji
Abstract : The current due to the H2 O2 reduction at Pt electrodes in H2 SO4 solutions shows a period-1 oscillation in the potential region of upd-H. As reported before ( ECS Transactions 69 (2015) 47), when Na2 SO4 is added to the solutions, the oscillation exhibits bifurcation behavior: it changes into complex oscillations such as mixed-mode, chaotic, and period- n oscillations. We have tentatively suggested that a non-covalent interaction between adsorbed OH, which is the reaction intermediate of the H2 O2 reduction, and Na + plays a crucial role for the bifurcation. In this work, the complex oscillations are found to be caused by an impurity in a commercially available Na2 SO4 reagent with a purity of 99.0%. The impurity is identified as Br - and its amount in the reagent is estimated to be more than 11 ppm. The bifurcation behavior can detect a trace of Br - in solutions containing a large amount of sulfate ions.